2018
DOI: 10.1063/1.5019890
|View full text |Cite
|
Sign up to set email alerts
|

An investigation of the sites occupied by atomic barium in solid xenon—A 2D-EE luminescence spectroscopy and molecular dynamics study

Abstract: A detailed characterisation of the luminescence recorded for the 6p P-6s S transition of atomic barium isolated in annealed solid xenon has been undertaken using two-dimensional excitation-emission (2D-EE) spectroscopy. In the excitation spectra extracted from the 2D-EE scans, two dominant thermally stable sites were identified, consisting of a classic, three-fold split Jahn-Teller band, labeled the blue site, and an unusual asymmetric 2 + 1 split band, the violet site. A much weaker band has also been identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 29 publications
2
23
0
Order By: Relevance
“…All the "intuitive" accommodations possess high symmetry that unavoidably leads to characteristic triplet Jahn-Teller structure of the S → P absorption and excitation bands. It becomes a custom to explain the lack of such structure in the spectra and assign the bands with different shapes to atoms located at grain boundaries and other defects [12]. However, the powerful intuitive arguments do not account for lattice relaxation, which may well contribute to minimization of the accommodation energy and eventually lead to counter-intuitive structures.…”
Section: Introductionmentioning
confidence: 99%
“…All the "intuitive" accommodations possess high symmetry that unavoidably leads to characteristic triplet Jahn-Teller structure of the S → P absorption and excitation bands. It becomes a custom to explain the lack of such structure in the spectra and assign the bands with different shapes to atoms located at grain boundaries and other defects [12]. However, the powerful intuitive arguments do not account for lattice relaxation, which may well contribute to minimization of the accommodation energy and eventually lead to counter-intuitive structures.…”
Section: Introductionmentioning
confidence: 99%
“…Obtaining large numbers of photons from single barium atoms in these matrix sites would benefit from a method to overcome bleaching, e.g., with repumping lasers. The barium emission peak at 619 nm, although not reported in some deposits made at 10 K [14,15], is more prominent in annealed deposits or deposits made at higher temperature and observed at 10 K [7,16]. The 619 nm peak is attributed in this work to barium atoms in a single vacancy (SV) site.…”
mentioning
confidence: 66%
“…Significant progress on understanding the spectroscopy of Ba in SXe has been made [7,14,15]. Through theoretical modeling, the strongest fluorescence peaks at 577 and 591 nm are identified as barium atoms in 5-atom and 4-atom vacancy sites in the SXe matrix [15]. These two fluores-cence peaks bleach fairly rapidly at high laser intensity, e.g.…”
mentioning
confidence: 99%
“…Finally, a discussion of the possible sites occupied in the three Ba/RG systems is provided based on the polarizability plots and the recent theoretical work done on the Ba/Xe system. 1…”
Section: The Journal Of Physical Chemistry Amentioning
confidence: 99%
“…With the inclusion of data for the Ba/Ar and Ba/Kr systems, the present contribution expands the matrix emission data and, in so doing, provides a more comprehensive analysis of the site attributions published by us recently for Ba/Xe. 1 The first Ba/rare gas (RG) matrix luminescence spectra were reported more than three decades ago by Balling and Wright 2 (B&W), while results for Ba/Ar and Ba/Xe were published recently by Fairbank and coworkers. 3 B&W's emission spectra are, however, not consistent with those recorded in the present study as shown by the red traces in Figure 1, even though both were produced with photoexcitation of the dominant (6s6p) 1 P 1 absorption bands.…”
Section: Introductionmentioning
confidence: 99%